Dilema Hukum Dalam Tradisi Kawin Tangkap di Sumba - Sarah, Keisha Alea; Sianipar, Christiano Hosea; Ariefandi, Nayna Carissa Putri; Shadilla, Muhammad Raihan; Tarina, Dwi Desi Yayi (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The kawin tangkap tradition in Sumba is a customary practice still upheld by some communities as part of their cultural heritage. However, from a civil law perspective, this tradition poses legal dilemmas due to its coercive nature in forming civil relations, particularly marriage, which should be based on the free consent of both parties. This practice ofte n contradicts key principles of civil law such as consent, free will, and the protection of individual rights, especially for women as legal subjects. this research examines how civil law interprets the legality of the kawin tangkap tradition and analyzes the conflict between customary norms and the national legal system. Using a normative and socio-juridical approach, this study proposes solutions to harmonize customary law and civil law through state intervention that ensures legal protection while respecting local wisdom.